STUDY OF WAVE AND TIDAL CURRENTS AT THE COASTAL WATERS OF PASIR JAMBAK PADANG CITY WEST SUMATRA PROVINCE - Farid Ramadan; Afrizal Tanjung; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in July 2016 at the coastal waters of Pasir Jambak Padang City West Sumatera Province with intention to determine the characteristics of wave and tidal currents. The stasion observation way is determined by using a purposive method. Research location divided into three stations, where each station consists of three sampling points, the distance between stations of approximately 100 m. Performed during 15 days of observation. Every station was placed parallel to the coastline, a distance less than 100 meters from the beach toward the Sea. High wave at high tide ranges from 0.21 - 0.33 m and 0.23 - 0.35 m at low tide. Wave period ranges from 1.54 to 2.23 seconds at high tide and 1.43 to 1.97 seconds at low tide. Wavelength ranges between 3.86 to 7.8 m at high tide and 3.35 to 6.08 m at low tide. Current velocity ranges between 0.37 to 0.64 m/sec at high tide and 0.36 to 0.51 m/sec at low tide. At the high tide the flow towards the southeast and at the low tide towards to the southwest.Key words: Current, Wave, Pasir Jambak, Padang, West Sumatra